Simulation of liquefied petroleum gas jet in combustion chamber of spark ignition engine - Ga, Bui Van; Dung, Duong Viet; Nam, Tran Van (Vietnam Journal of Mechanics, 2002)
Based on the mathematical validated by experimental data, the present paper introduces the evolution of concentration and velocity fields of Liquefield Petroleum Gas (LPG) jet in combustion chamber of spark ingnition enegine under effects of injection conditions and surrounding environment. The results allow us to predict the development of jet for an efficient organization of mixture preparation and combustion process in LPG direct injection spark ignition engine